Contrast of nuclei in stratified squamous epithelium in optical coherence tomography images at 800 nm. Issue 9 (3rd June 2019) - Chen, Si; Liu, Xinyu; Wang, Nanshuo; Ding, Qianshan; Wang, Xianghong; Ge, Xin; Bo, En; Yu, Xiaojun; Yu, Honggang; Xu, Chenjie; Liu, Linbo
Abstract: Imaging nuclei of keratinocytes in the stratified squamous epithelium has been a subject of intense research since nucleus associated cellular atypia is the key criteria for the screening and diagnosis of epithelial cancers and their precursors. However, keratinocyte nuclei have been reported to be either low scattering or high scattering, so that these inconsistent reports might have led to misinterpretations of optical images, and more importantly, hindered the establishment of optical diagnostic criteria. We disclose that they are generally low scattering in the core using Micro‐optical coherence tomography (μOCT) of 1.28‐μm axial resolution in vivo; those previously reported "high scattering" or "bright" signals from nuclei are likely from the nucleocytoplasmic boundary, and the low‐scattering nuclear cores were missed possibly due to insufficient axial resolutions ( 4μm). It is further demonstrated that the high scattering signals may be associated with flattening of nuclei and cytoplasmic glycogen accumulation, which are valuable cytologic hallmarks of cell maturation. Abstract : The nuclei of the stratified squamous epithelium have been reported to be either low scattering or high scattering. Using micro‐optical coherence tomography, we demonstrate that the nuclei are low scattering in the core; those previously reported "high‐scattering" signals are likely from the nucleocytoplasmic boundary. This study clarifies the optical characteristics of the nuclei which have important significance for the establishment of diagnostic criteria for epithelial cancers.